The role of women in peace diplomacy: advancement and challenges - Drozd, Natalya I. (Journal of the Belarusian State University. International Relations, 2022)
We consider the role of women in strengthening of international peace and security. Specifically, we examine how this role has evolved in history and is performed at present. There is abundant evidence to show that a gender-inclusive and well-integrated peace process increases the probability of lasting peace. In light of this evidence, we present an argument for more extensive involvement of women in peace diplomacy as politicians and diplomats.